Future Impact of mRNA Therapy on Cardiovascular Diseases - John P. Cooke; Keith A. Youker (Methodist DeBakey Cardiovascular Journal)
The silver lining of the recent pandemic was that it accelerated the emergence of messenger ribonucleic acid (mRNA) therapeutics. The great promise of mRNA therapeutics was highlighted by the speed at which the vaccines were created, tested, and proven to be relatively safe and highly effective. There are a wide variety of mRNA therapeutics now under development, and dozens of these are in clinical trials. These therapeutics are generating a major paradigm shift in medical therapy, including the treatment of cardiovascular disease. Most of the cardiovascular mRNA therapies are still in preclinical development, although a phase 2a trial of mRNA therapy for myocardial ischemia has been completed with promising results.1 The application of mRNA therapies to cardiovascular diseases is virtually limitless, and ongoing work includes mRNA therapies for myocardial ischemia, heart failure, arrhythmias, hypercholesterolemia, and arterial occlusive diseases. In addition, mRNA may be used to enhance cell therapies. In the future, mRNA therapies for cardiovascular disease are destined to supplant some of our current biologics and pharmacotherapies and will be used to treat previously untreatable cardiovascular diseases. Furthermore, mRNA therapies can be personalized, and they can be rapidly generated in current Good Manufacturing Practice facilities with a modest footprint, facilitating the rise of hospital-based regional centers of RNA therapeutics.